A characterization of farsightedly stable networks - Gilles Grandjean; Ana Mauleon; Vincent Vannetelbosch (Games, 2010)
We study the stability of social and economic networks when players are farsighted. We first provide an algorithm that characterizes the unique pairwise and groupwise farsightedly stable set of networks under the componentwise egalitarian allocation rule. We then show that this set coincides with the unique groupwise myopically stable set of networks but not with the unique pairwise myopically stable set of networks. We conclude that, if groupwise deviations are allowed then whether players are farsighted or myopic does not matter; if players are farsighted then whether players are allowed to deviate in pairs only or in groups does not matter.
Keywords: 330; farsighted players; pairwise deviations; groupwise deviations